2020
DOI: 10.1016/j.redox.2020.101712
|View full text |Cite
|
Sign up to set email alerts
|

JNK signalling regulates antioxidant responses in neurons

Abstract: Reactive oxygen species (ROS) are generated during physiological bouts of synaptic activity and as a consequence of pathological conditions in the central nervous system. How neurons respond to and distinguish between ROS in these different contexts is currently unknown. In Drosophila mutants with enhanced JNK activity, lower levels of ROS are observed and these animals are resistant to both changes in ROS and changes in synapse morphology induced by oxidative stress. In wild type flies,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…We found that MKK7, but not MKK4, participated in mechanical overloading-induced JNK activation. Although JNK signalling plays a key role in cell proliferation, differentiation and apoptosis in response to stress, the contributions of MKK7–JNK in cartilage ageing and OA progression in response to mechanical stress are not known 48 49. In the present study, we found that FBXW7 inhibition by excessive mechanical loading strongly elevated MKK7 expression and subsequently induced an increase in the JNK signal in chondrocytes, resulting in enhanced cell senescence.…”
Section: Discussionmentioning
confidence: 43%
“…We found that MKK7, but not MKK4, participated in mechanical overloading-induced JNK activation. Although JNK signalling plays a key role in cell proliferation, differentiation and apoptosis in response to stress, the contributions of MKK7–JNK in cartilage ageing and OA progression in response to mechanical stress are not known 48 49. In the present study, we found that FBXW7 inhibition by excessive mechanical loading strongly elevated MKK7 expression and subsequently induced an increase in the JNK signal in chondrocytes, resulting in enhanced cell senescence.…”
Section: Discussionmentioning
confidence: 43%
“…We next asked whether functional PPARγ is also required for the therapeutic outcome of ASK1 inhibitors in proteasomal inhibition [ 49 ]. To this end, PPARγ in the liver was depleted by adenovirus, and mice were treated with selonsertib and bortezomib to monitor proteotoxicity ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has also shown that in neurons, JNK is activated specifically by oxidative stress and activates c-jun containing AP-1 transcription factors independently of c-Fos. This specific c-jun activation results in an increased abundance of the antioxidant protein SRXN-1 [ 46 ]. Thus, the strong activation of c-jun we detected in 5xFAD lysates at 10 months could represent an attempt to counteract the decrease in GST.…”
Section: Discussionmentioning
confidence: 99%